Mucosal immunity in upper and lower respiratory tract to MERS-CoV - Shrwani, Khalid J.; Mahallawi, Waleed H.; Mohana, Abdulrhman I.; Algaissi, Abdullah; Dhayhi, Nabil; Sharwani, Nouf J.; Gadour, Eyad; Aldossari, Saeed M.; Asiri, Hasan; Kameli, Nader; Asiri, Ayad Y.; Asiri, Abdullah M.; et al. (Frontiers in Immunology, 2024)
Introduction: Middle East respiratory syndrome coronavirus (MERS-CoV) has emerged as a deadly pathogen with a mortality rate of up to 36.2%. MERS-CoV can cause severe respiratory tract disease and multiorgan failure. Therefore, therapeutic vaccines are urgently needed. This intensive review explores the human immune responses and their immunological mechanisms during MERS-CoV infection in the mucosa of the upper and lower respiratory tracts (URT and LRT). Objective: This study aims to provide a valuable, informative, and a critical summary of the protective immune mechanisms against MERS-CoV infection in the U/LRT for the purpose of preventing and controlling MERS-CoV disease and designing effective therapeutic vaccines. Methods: In this review, we focus on the immune potential of the respiratory tract following MERS-CoV infection. We searched in PubMed, Embase, Web of Science, Cochrane, Scopus, and Google Scholar using the following terms: “MERS-CoV”, “B cells”, “T cells”, “cytokines”, “chemokines”, “cytotoxic”, “upper and lower respiratory tracts”. Results: We found and included 152 studies in this review. We are reporting that the cellular innate immune response, including macrophages, dendritic and natural killer cells, produces antiviral substances such as interferons and interleukins to prevent the virus from spreading. In the adaptive and humoral immune responses, CD4+ helper T cells, CD8+ cytotoxic T cells, B cells, and plasma cells protect against MERS-CoV infection in URT and LRT. Conclusion: The human nasopharynx-associated lymphoid tissue (NALT) and bronchus-associated lymphoid tissue (BALT) could successfully limit the spread of several respiratory pathogens. However, in the case of MERS-CoV infection, limited research has been conducted in humans with regard to immunopathogenesis and mucosal immune responses due to the lack of relevant tissues. A better understanding of the immune mechanisms of the URT and LRT is vital for the design and development of effective MERS-CoV vaccines.